Solid-State Transformations of Fluoroquinolones Induced by Mechano- and Tribo-Chemical Processes - Kadri, Lena (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2025)
Mechano- and tribo-chemistry is growing at a fast rate. However, more scientific contributions need to be made in order to better understand this type of chemistry and processing so that it can be implemented into the future of pharmaceuticals. This project aims to advance the understanding of the kinetic, mechanistic, and solid-state behavior of ball milled fluoroquinolone drug(s) (LVXh and/or CIP), both in the presence and absence of polymer(s), using mechano- and tribo-chemistry techniques. Furthermore, the poor solubility of APIs is a huge challenge that continues to face the pharmaceutical industry today. Amorphization is a known solution to this problem, although it presents its own challenges, such as poor stability. Therefore, binary and ternary amorphous polymeric systems were generated to improve the solubility of CIP and the poor stability of the amorphous form. The enhancement of the solubility of CIP, the stability of the systems after solid-state solubility studies, and the antibacterial activity of the systems were investigated.
APPROVED